The Black Mirror—Stories: Creating A Short Story Collection Highlighting Beauty Penalty Phenomenon in the Indonesian Society - Natasya Aurelia Puspo; Stefanny Irawan (Institute of Research and Community Outreach - Petra Christian University, 2025)
Beauty penalty is a phenomenon which occurs in society which imposes disadvantages on attractive people. However, as this phenomenon has largely been acknowledged in the confinement of one individual’s testimony to another without adequate further study, the majority of people still ignore it. Despite its prevalence and significance, the beauty penalty phenomenon lacks deeper discussion, especially in Indonesia. In response to this reality, this paper explores the triggers to beauty penalty and multiple forms which the beauty penalty affects one’s life using the concept of perceived entitlement by Margaret Lee et al., the concept of unmet expectations by Catherine Eckel and Rick Wilson, and the concept of beauty penalty forms by Stephen Marson and Joanne Hessmiller as the theoretical framework. We explore this topic by designing a short story collection to show how people’s perceived entitlement and unmet expectations of the attractive protagonists as the triggers to beauty penalty occurrence. In addition, the work shows that the beauty penalty phenomenon can manifest in forms such as social penalties, mental problems, emotional disturbances, and physical challenges. Thus, the protagonists must face their own forms of beauty penalty to achieve their goals.